Knowing the Basics about 4-H Clubs - Marilyn N. Norman; Joy C. Jordan (EDIS)
Revised! 4HS-FS101.6, a 4-page fact sheet by Marilyn N. Norman and Joy C. Jordan, is part of the 4-H 101 Fact Sheets series.  It explains what a 4-H club is, who can join, criteria for 4-H youth development programming, types of 4-H clubs, starting and maintaining 4-H clubs, fiscal requirements, and evaluating club performance. Published by the UF 4-H Youth Development Program, July 2009.